ANALISIS DESKRIPTIF PERSEPSI MASYARAKAT TERHADAP PELEMAHAN NILAI RUPIAH SERTA DAMPAKNYA TERHADAP HAK EKONOMI DAN KESEJAHTERAAN MASYARAKAT - Rowlan Takaya; Virna Zulfitri; Kania Sania Ekaputri (STMIK Widuri Jakarta, 2026)
The weakening of the rupiah is an economic issue that can impact various aspects of people's lives. This situation is usually associated with rising prices of goods and services, changes in people's shopping habits, decreased purchasing power, and public welfare. This study aims to determine how the public perceives the impact of the weakening rupiah on their economic rights and welfare. This study used a quantitative descriptive method, collecting data through an online questionnaire administered to 52 respondents. The data were analyzed using descriptive statistics in percentage form and based on relevant literature. The study showed that most interviewees felt that the weakening rupiah was related to the rising cost of living and changes in how people spend their money. Most respondents also stated that this situation has led to decreased purchasing power, increased anxiety about job and income stability, and is closely related to the level of public welfare. Furthermore, most respondents stated that people still have the right to a decent life, and the government has an obligation to ensure the people's welfare. According to respondents, the weakening rupiah impacts not only the economic aspect but also the fulfillment of economic rights and public welfare. So, all parties, including the government, must work together to maintain economic stability and help improve the people's welfare.